Kewenangan OJK Dalam Pengawasan Pasar Uang Syariah dan Surat Berharga Syariah: Tinjauan Hukum Ekonomi Syariah di Indonesia - Imon, Syarah Adilla (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The Financial Services Authority (OJK) plays a strategic role in regulating and supervising the national financial system, including the growing Islamic financial sector in Indonesia. This study aims to analyze OJK's authority in supervising the Islamic money market and Islamic securities from the perspective of Islamic economic law. Using a normative juridical method, this research examines the legal framework underpinning OJK's role, such as Law Number 21 of 2011 concerning OJK, along with implementing regulations related to Islamic financial instruments. The findings show that OJK holds broad authority in overseeing the Islamic money market and Islamic securities, including licensing, regulation, and enforcement of compliance with sharia principles. However, challenges remain in harmonizing OJK regulations with the fatwas of the National Sharia Council (DSN-MUI), as well as improving financial literacy and supervision in the Islamic fintech sector. This study recommends strengthening inter-agency coordination and aligning positive law with the principles of fiqh muamalah as strategic steps to promote a healthy and sustainable Islamic financial system.